Paracetamol use in early life and asthma: prospective birth cohort study. (15th September 2010) - Lowe, Adrian J; Carlin, John B; Bennett, Catherine M; Hosking, Clifford S; Allen, Katrina J; Robertson, Colin F; Axelrad, Christine; Abramson, Michael J; Hill, David J; Dharmage, Shyamali C
Abstract : Objective To determine if use of paracetamol in early life is an independent risk factor for childhood asthma. Design Prospective birth cohort study. Setting Melbourne Atopy Cohort Study. Participants 620 children with a family history of allergic disease, with paracetamol use prospectively documented on 18 occasions from birth to 2 years of age, followed until age 7 years. Main outcome measures The primary outcome was childhood asthma, ascertained by questionnaire at 6 and 7 years. Secondary outcomes were infantile wheeze, allergic rhinitis, eczema, and skin prick test positivity. Results Paracetamol had been used in 51% (295/575) of children by 12 weeks of age and in 97% (556/575) by 2 years. Between 6 and 7 years, 80% (495/620) were followed up; 30% (148) had current asthma. Increasing frequency of paracetamol use was weakly associated with increased risk of childhood asthma (crude odds ratio 1.18, 95% confidence interval 1.00 to 1.39, per doubling of days of use). However, after adjustment for frequency of respiratory infections, this association essentially disappeared (odds ratio 1.08, 0.91 to 1.29). Paracetamol use for non-respiratory causes was not associated with asthma (crude odds ratio 0.95, 0.81 to 1.12). Conclusions In children with a family history of allergic diseases, no association was found between early paracetamol use and risk of subsequent allergic disease after adjustment for respiratory infections or when paracetamol use was restricted to non-respiratory tract infections. These findings suggest that early paracetamol use does not increase the risk of asthma.